Estado, educação e religiosidade: atuação judicial na esfera privada da família religiosa protestante calvinista e a teoria de Robert Alexy - Brito, Aubério da Silva (2015)
This research, exploratory, descriptive, qualitative approach, part of two questions: 1) there are tensions between the religious speech calvinist and the discourse of the judges surveyed about the limits of State intervention in the private sphere of families calvinists, in application of the existing rules that deal with the education of the child? 2) in the discourse of these magistrates investigated is possible to identify signs of the use of the Theory of the Weighting of Robert Alexy, as proper technique for resolving possible conflicts between the rights of the child and the religious freedom of parents in those families? Initially, it presents the process of historical coexistence between the public sphere of the State and the private sphere of the Church, especially in Brazil. After long harmonious coexistence between those spheres, occurred consequent transition between the old model of State, before ruled by religious perspective, and the current model, considered as a Secular State. However, even if there are competent constitutional precept national that underlies the definitive separation between Church and State, in practice, this is not completely effective. This relationship is not free from mutual influences. Using the analysis of discourse as methodological approach, we sought to interview four judges and three theologians calvinists. The discourse of research subjects investigated, confirm the hypothesis that, in certain cases, there are tensions between the values upheld by the State and the values upheld by religious. Notably, this is proven by examining the distances between the principles contained in the conceptions religious of protestant ideals of John Calvin, as the educational formation of the child in the private life of calvinist family, in the face of modern principles contained in the statutes protective of the rights of the child, imposed by State. Taking as a starting point the Law "Boy Bernardo", amending device contained in the Statute of the Child and the Adolescent, it seeks to understand the problem in light of the thought of Robert Alexy. The analysis has demonstrated that the theory of the Weighting of Alexy provides the calibration of the application of the legal standard in this case. To obey the submaximal of appropriateness, necessity and proportionality in the strict sense of the term, reaches the end of preserving the modern children's rights without violating the right to religious freedom of parents in educating their children. In his speech the magistrates investigated say adopt this technology, although alert that part of their peers perform weighting, without a methodological justification as taught by Alexy. The research concludes by indicating that the judicial intervention in the private lives of families religious protestants will be adequate and minimized from the correct application of the technique of weighting in alexyanos molds.